Iceman (2011), volume 1 ebook Thawing out. - Grace, Sina (Iceman (2011), 2017)
Collects: Iceman (2017) #1-5. Bobby Drake has been in the super-hero game longer than most — but what is he known for besides a few good one-liners and a string of failed relationships? The time is now or never for Bobby to build a life and legacy he can be proud of — and become the best Iceman he can be! But whether seeking ex-girlfriend Kitty Pryde's advice on meeting guys or delivering his latest news to his parents, it won't be easy — and that's before a gang of revenge-seeking Purifiers comes calling! Still learning to be comfortable in his own skin, Bobby will meet someone who's perhaps too comfortable in his: the Son of Wolverine himself, Daken! But when the moment of truth arrives, which is worse for Iceman: facing his parents — or the Juggernaut?